A highly sensitive fluorescent probe for detection of hydrazine in gas and solution phases based on the Gabriel mechanism and its bioimaging. Issue 75 (26th July 2016) - Maji, Rajkishor; Mahapatra, Ajit Kumar; Maiti, Kalipada; Mondal, Sanchita; Ali, Syed Samim; Sahoo, Prithidipa; Mandal, Sukhendu; Uddin, Md Raihan; Goswami, Shyamaprosad; Quah, Ching Kheng; Fun, Hoong-Kun
Abstract : A new probe 2-benzo[1, 2, 5]thiadiazol-4-yl-isoindole-1, 3-dione (BTI) based on the Gabriel reaction was developed for hydrazine which shows promising selectivity towards hydrazine over other analytes. Abstract : A new probe 2-benzo[1, 2, 5]thiadiazol-4-yl-isoindole-1, 3-dione (BTI ) based on the Gabriel reaction mechanism was synthesized and characterized for the specific detection of hydrazine with high selectivity against other amines in an organo-aqueous solution. Upon hydrazinolysis ofBTI in the presence of hydrazine in a H2 O–DMSO (4 : 6, v/v) solution (10 mM HEPES buffer, pH 7.4) at room temperature, the chemosensor produces fluorescent aminobenzthiadiazole with a maximum emission at 498 nm along with a color change from colorless to green, allowing selective colorimetric and fluorometric detection of hydrazine by the naked eye. ProbeBTI was also successfully applied in vapor phase hydrazine detection into a solid state over other interfering volatile analytes. Furthermore, the probeBTI coated with silica gel TLC plates could act as a visual and fluorimetric probe for hydrazine vapor detection. The experimental detection limit of hydrazine is 2.9 ppb, which is well below the accepted limit (10 ppb) for hydrazine set by the U.S. Environmental Protection Agency (EPA). DFT and TDDFT calculations were performed in order to demonstrate the sensing mechanism and the electronic properties of probe and hydrazinolysis products. Additionally, probeBTI could also be applied for the imaging of hydrazine in living cells.